From waste to innovation: Bioentrepreneurship skills through project-based learning in biology education - Nuzula Khoiro Ummah; Nur Ducha; Dyah Hariani; Endang Susantini; Fida Rachmadiarti; Muhammad Fajar Faliasthiunus Pradipta (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Project-Based Learning (PjBL) offers a relevant approach for linking biology education with sustainability and entrepreneurship. However, existing studies have generally examined PjBL, entrepreneurship education, and biological waste utilization separately, leaving limited understanding of how their integration can foster bioentrepreneurship. Objectives: This review aimed to analyze the role of PjBL in developing bioentrepreneurship skills, particularly through biological waste utilization. Methods: A Systematic Literature Review (SLR) was conducted on ten Scopus-indexed articles, complemented by bibliometric analysis using VOSviewer. Results: Topics such as "project" and "bioentrepreneurship" are more frequently discussed, while other themes like "implementation" and "PBL" require further exploration. The components of reflection and authentic assessment were found to be dominant factors in the development of entrepreneurial competencies. The implementation of PjBL in biological waste management creates a learning ecosystem that integrates circular economy principles with constructivist pedagogy, as well as providing real-world experience in creating products of economic value. Implementation challenges include the need for laboratory infrastructure, prototyping facilities, institutional support, and external stakeholder involvement. Conclusion: PjBL is a promising pedagogical approach for developing bioentrepreneurship competencies through sustainable, innovation-oriented learning.